2014
DOI: 10.1108/ijhcqa-06-2013-0072
|View full text |Cite
|
Sign up to set email alerts
|

Medical record-keeping and patient perception of hospital care quality

Abstract: A modest relationship exists between the quality of medical-record keeping and patient perception of hospital care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…However, the reduced completeness in drug therapy items could be a predictor of poor quality of care [ 10 , 11 , 23 ]. These findings are consistent with prior research [ 12 , 18 ] and suggested that further investments and attention should be put on doctors behaviour in order to prevent potentially harmful consequences for patient safety [ 11 , 12 , 23 ]. Despite the results obtained in themes and moments, there is the opportunity to improve performance as far as levels are concerned, achieving a better completeness in the Level 2 -management and Level 3 -re-assessment, pursuing a better quality of care.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, the reduced completeness in drug therapy items could be a predictor of poor quality of care [ 10 , 11 , 23 ]. These findings are consistent with prior research [ 12 , 18 ] and suggested that further investments and attention should be put on doctors behaviour in order to prevent potentially harmful consequences for patient safety [ 11 , 12 , 23 ]. Despite the results obtained in themes and moments, there is the opportunity to improve performance as far as levels are concerned, achieving a better completeness in the Level 2 -management and Level 3 -re-assessment, pursuing a better quality of care.…”
Section: Discussionsupporting
confidence: 91%
“…A complete and accurate CR can help achieve safer practices [ 2 ], such as better communication and medication reconciliation, which are common reasons for medical errors worldwide [ 9 – 11 ]. Several authors reported that poor quality of the information in CR may be a predictor of poor quality of care [ 3 , 12 16 ], and may be associated with higher rates of adverse patient safety events [ 2 , 15 ]. This is true particularly considering adverse drug events, that may be caused by prescribing error in prescription writing, that involved illegibility, ambiguous abbreviations or lack of important piece of information such as date of prescription, dose or route of administration [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 12 ] No independent associations between patient pain perception scores and documented pain assessments or nutritional disorder screening results were reported. [ 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Daily documentation and maintenance of medical record quality is a crucial issue in orthopaedic surgery ( 1 ). Medical record denotes the main information support used by healthcare providers ( 2 ). Although medical records serve many functions, their primary purpose is to record information about patients and their care ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%